To compare the functions \( f(x) \) and \( g(x) \) based on the provided table, we can look at the values at each corresponding \( x \) value:
\[ \begin{array}{|c|c|c|} \hline x & f(x) & g(x) \ \hline -2 & -1 & -1 \ -1 & 34 & 0 \ 0 & 1 & 1 \ 1 & 114 & 2 \ 2 & 3 & 3 \ \hline \end{array} \]
Now, we'll determine where \( f(x) \) is greater than \( g(x) \):
- At \( x = -2 \): \( f(-2) = -1 \) and \( g(-2) = -1 \) → \( f(-2) \) is not greater.
- At \( x = -1 \): \( f(-1) = 34 \) and \( g(-1) = 0 \) → \( f(-1) \) is greater.
- At \( x = 0 \): \( f(0) = 1 \) and \( g(0) = 1 \) → \( f(0) \) is not greater.
- At \( x = 1 \): \( f(1) = 114 \) and \( g(1) = 2 \) → \( f(1) \) is greater.
- At \( x = 2 \): \( f(2) = 3 \) and \( g(2) = 3 \) → \( f(2) \) is not greater.
From this analysis, \( f(x) \) is greater than \( g(x) \) at \( x = -1 \) and \( x = 1 \).
Thus,
\( f(x) \) is greater than \( g(x) \) when \( -1 < x < 1 \).
Therefore, the answer is:
\( f(x) \) is greater than \( g(x) \) when \( -1 < x < 1 \).